FOREIGN MODELS OF STATE REGULATION OF THE CREDIT SERVICES MARKET - Allamurodova Khanzoda Kurbanmurad's daughter (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article discusses foreign models of state regulation of the credit services market. According to the author, the governments of foreign countries took an active part in maintaining the liquidity of credit organizations through capitalization and refinancing. Prominent examples of such regulation are the French, Singapore and Hong Kong models, which were based on a successful combination of high levels of state intervention with regulatory tactics.